Fifth Five-Year Plan A Draft Out Line Government of Himachal Pradesh - Planning Commission (Planning Commission, 1974)
every year an unestimated volume of valuable soil is washed away by rains. The per capital holding of arable land is less than one hectare and to stretch the land for cultivation under mountainous conditions is extremely difficult, if not impossible,, Under these circumstances the return from agriculture to farmers is meagre.
Planning Department